Implementation of Patient-Reported Outcomes Measurement Information System (PROMIS) score for the assessment of factors influencing surgical outcome of lumbar spinal stenosis. (April 2022) - Rahman, Moshiur; Khan, Robert Ahmed; Ziauddin, Md; Hasan, Sheikh Mahmood; Rahman, Sabrina; Lozada-Martinez, Ivan David; Maan Al-Salihi, Mohammed; Rahman, Raphia; Moscote-Salazar, Luis Rafael
Abstract: Introduction: The surgical outcome of lumbar spinal stenosis is variable. Appropriate patient selection, surgical procedure, multi-level involvement, body mass index, mental stability, etc., are factors related to outcome. According to the patient's perspective, the Patient-Reported Outcomes Measurement Information System (PROMIS) gives clinicians and specialists admittance to dependable, substantial, and adaptable proportions of well-being status that evaluate physical, mental, and social prosperity. Objective: The purpose of this study is to identify the factors influencing the surgical success of patients with lumbar spinal stenosis. Methods: In this cross-sectional study, we have outlined the potential factors that have influenced the surgical outcome of lumbar spinal stenosis. A total of 146 patients were studied from 2010 to 2016. Results: In our study, the male and female ratio was 3:2. The mean age group was 60 years, range 50–70 years. The minimum follow-up was four years. PROMIS score was used to assess the outcome of surgery. We got the PROMIS score pre and postoperatively using online "orthotoolkit" questionnaires and calculated the patient's average scores. Decompressive laminectomy, laminotomy, unilateral approach-all procedures had similar outcomes. Conclusion: The outcome of surgical decompression is satisfactory, although various factors can be predictors of surgical failure. Our study suggests psychological issues, high BMI, comorbid conditions, multi-level surgeries are few that may predict poor outcomes. Highlights: The surgical outcome of lumbar spinal stenosis is variable. Surgical outcome of lumbar spinal stenosis depends on many factors. Goal of our surgery should be to improve the patients satisfaction.